Induction, Morphogenesis, and Germination of the Chlamydospore of Candida albicans - Jansons, Vilma K. (1970)
Early log phase yeast cells of Candida albicans transformed into suspensor cells and chlamydospores when streaked on washed agar without added nutrients. The transformation was apparently a result of endogenous metabolism since starved yeast cells did not form chlamydospores. Addition of glucose (5 mg/ml) to washed agar completely suppressed chlamydospore formation. Size of inoculum and age of inoculum markedly affected chlamydospore yield. Electron microscopy of thin sections revealed the chlamydospore wall to be double layered, the outer thin layer being continuous with the wall of the suspensor cell. A technique was devised to study germination of chlamydospores. Chlamydospores germinated by budding, and the fluorescent antibody technique was used to study the budding process.